Kajian Area Penyinaran Dan Nilai Intensitas Pada Peralatan Blue Light Therapy - Sri Santiari, Dewa Ayu; putra, mahadi (Majalah Ilmiah Teknologi Elektro; Vol 17 No 2 (2018): (May - Agustus) Majalah Ilmiah Teknologi Elektro, 2018)
The case of a yellow baby (hyperbilirubinemia) is one of the most common conditions in newborns. One of the measures to reduce bilirubin levels in a baby is by phototherapy using blue light therapy. There are two types of blue light therapy equipment that is currently used in Cempaka area of Sanglah hospital, namely: blue light therapy fluorescent lamps and blue light therapy LED lights. Both types of equipment have different shapes and light sources. The result of light source form analysis on both therapy equipment shows that blue light therapy of rectangular fluorescent lamp will produce a wider irradiation area than blue light therapy LED which only produce limited exposure area on work surface. Based on the area and the intensity of irradiation produced by the two forms of blue light therapy, it can be concluded that blue light therapy of rectangular fluorescent lamps at a distance of 30 cm will result in a wider irradiation area with a higher mean intensity value (12mW/cm 2 /nm) compared to blue light therapy LEDs that produce only limited irradiated areas on the surface of the work plane with lower average intensity values (6 mW/cm 2 /nm).